1999
DOI: 10.1128/jcm.37.7.2373-2375.1999
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Human Rotavirus G Types Circulating in Paris, France, during the 1997–1998 Epidemic: High Prevalence of Type G4

Abstract: Group A human rotavirus G genotypes were determined by means of reverse transcription-PCR in 170 stool specimens from children with acute diarrhea admitted to a Paris children’s hospital during a 1-year survey (1997 to 1998). The isolates all belonged to types G1 to G4, with type G4 predominating (60%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…The next most common type was P [8],G4, and the 3-year survey in Dijon showed clearly that this type emerged during the winter of 1997-1998. The predominance of type G4 has been reported in France in one hospital in Paris during the same period (7). In our study, either P [8],G1 or P [8],G4 was predominant according to the region.…”
supporting
confidence: 74%
“…The next most common type was P [8],G4, and the 3-year survey in Dijon showed clearly that this type emerged during the winter of 1997-1998. The predominance of type G4 has been reported in France in one hospital in Paris during the same period (7). In our study, either P [8],G1 or P [8],G4 was predominant according to the region.…”
supporting
confidence: 74%
“…Also, the combination of either Beg9 or sBeg9 with End9 or RVG9 (32) might be successful in amplifying G25, but the same combinations might not be able to pick up the novel G31 and G30 genotypes in PCR screening assays. Furthermore, the primer combination Beg9/sBeg9 and EndA (37) are likely to detect G25, but will be unsuccessful in case of G30 and G31 especially if the forward primer Beg9 is used. Considering VP4, both forward primers, VP4-1-17F (38) and Con3 (31) in combination with the reverse primer Con2 will be sub-optimal in detecting any of the P genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…As children <14 years of age comprise 42AE2% of the total Kenyan population (c. 37 953 840) (Central Intelligence Agency, 2009) and as RVs have been identified as an important cause of paediatric viral gastroenteritis in Kenya (Kiulia et al , 2008(Kiulia et al , 2009, the group A RVs detected in the surface water sources and sewage were genotyped to gain further insight into the RVs circulating in the water sources and surrounding communities. In this investigation, the group A RV G typing methods, as described by Gouvea et al (1990Gouvea et al ( , 1994a, Das et al (1994), Gault et al (1999) and Iturriza-Gó mara et al (2004), were successfully applied to type 95AE5% of the RVs detected in the Kenyan surface water and sewage samples. This typing rate is comparable to that reported by van Zyl et al (2006) who identified the G types in 94AE7% of the RV-positive environmental water samples in South Africa compared to the typing rate of 70 and 43AE6% reported for Egypt and Spain, respectively (Villena et al 2003b), and 20% reported for Brazil (Miagostovich et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…RVs are classified according to G and P genotypes and may be called a strain, genotype or type. Multiplex nested PCR methods and primers initially developed for the G typing (Gouvea et al 1990(Gouvea et al , 1994aDas et al 1994;Gault et al 1999;Iturriza-Gó mara et al 2004) and the P typing (Gentsch et al 1992;Gouvea et al 1994b;Mphahlele et al 1999;Simmonds et al 2008) of human and animal RVs from clinical samples were applied for the characterization of the VP7 (G types) and the VP4 (P types) genes of the strains from RV-positive samples.…”
Section: Typing Of Rotavirusesmentioning
confidence: 99%